Pola Pemenuhan Kebutuhan Pendidikan Anak pada Keluarga Single Mother Parent di Desa Pemongkong Kecamatan Jerowaru - Muhammad Aziz; Suud Suud; Hairil Wadi (Yayasan Literasi Sains Indonesia, 2026)
This study aims to identify and analyze how the pattern of fulfilling children's educational needs in single mother parent families in Pemongkong Village, Jerowaru District. This study uses a qualitative approach and case study method. With the types of data are primary data and secondary data. While the subjects in this study are single mother parents who are directly involved and play a role in fulfilling children's educational needs. Informants in this study are the head of the Pemongkong Village Area and neighbors who directly observe the activities of single mother parents while working and know about the topic or problem in the study, and elementary school teachers who are considered to be able to provide additional information related to the research topic. The data collection methods applied include observation, interviews, and documentation. The data analysis process in this study was carried out through three stages, namely: 1) data reduction; 2) data presentation; and 3) drawing conclusions. Meanwhile, the validity of the data was tested using data triangulation techniques including 1) source triangulation; 2) technical triangulation; 3) and time triangulation. The results of this study indicate that there are 3 patterns of fulfilling children's educational needs by single mother parents: 1) exchange; 2) making/producing; 3) and asking.